ETHICAL CONSIDERATIONS IN PHARMACEUTICAL ANALYTICS: BALANCING INNOVATION AND PATIENT PRIVACY - Harpeet Singh, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article investigates the ethical dimensions of implementing advanced analytics in pharmaceutical research and development, focusing on the intersection of technological innovation and patient privacy protection. Through analysis of implementation data from 500+ pharmaceutical organizations and examination of over 2,000 privacy incident reports, we identify critical patterns in both successful and failed privacy protection strategies. The findings reveal that organizations implementing multi-layered security architectures achieve 99.95% privacy preservation rates, while those relying on single-layer protection experience breach rates 3.5 times higher. The article demonstrates that successful bias mitigation strategies can reduce algorithmic performance disparities from 12% to under 2% across demographic groups. Cost-benefit analysis indicates that proactive privacy investments, averaging $2.8M initially and $900K annually, result in 195% ROI over three years through breach prevention and improved operational efficiency. Propose a novel framework for ethical implementation that combines federated learning architecture (achieving 99% accuracy retention) with differential privacy integration (ε ≤ 0.8), supported by a structured ethics governance model requiring 30% patient representation. The recommendations provide a practical roadmap for pharmaceutical organizations to advance innovation while maintaining robust privacy protections and ethical standards.